A National Study of Tetanus Vaccine Knowledge, Receipt and Acceptance Among Emergency Department Patients - Francesco Sergi; Elisa Vaezazizi; Shaokui Ge; Christopher Alvarez; Jesus Torres; Brian Chinnock; Michael Gottlieb; Vijaya Arun Kumar; Kristin L. Rising; Efrat Rosenzweig Kean; Stephanie Eucker; Robert M. Rodriguez (Academic Emergency Medicine, 2026)
ABSTRACT Objective The Tetanus, Diphtheria, Pertussis (Tdap, “tetanus”) vaccine is recommended for adults every 10 years. In a national sample of adult emergency department (ED) patients, we sought to determine (1) knowledge and up‐to‐date status of the tetanus vaccine; (2) reasons for nonreceipt of the vaccine; (3) vaccine acceptability if offered in the ED; and (4) reasons for nonacceptance in the ED if offered. Methods This was a cross‐sectional survey study among non‐critically ill adults at 10 US EDs, asking questions about knowledge, receipt, and acceptability of the tetanus vaccine. Vaccine receipt was determined by self‐report. Aggregate responses are reported as descriptive statistics. Logistic regression modeling was performed, and data are presented as adjusted odds ratios (aOR) with 95% confidence intervals (CIs). Results Of 4326 patients approached, 3285 (75.9%) agreed to participate, and 5 were excluded because of incomplete responses. Among 3280 participants, 13.4% had not heard of the vaccine; and 58.0% were not up‐to‐date. Factors associated with not being up‐to‐date included age 34–48 (aOR 0.65; 95% CI 0.53–0.81), African American race (aOR 1.46; 95% CI 1.19–1.79), no primary care doctor (aOR 1.29; 95% CI 1.04–1.61) and no insurance (aOR 1.86; 95% CI 1.36–2.56). Among participants not up‐to‐date, 21.6% would accept it during their ED visit. Primary reasons for nonacceptance were needing more information, concerns about side effects, and preference to get it from their doctor. Conclusions Over half of adult ED patients are not up‐to‐date on the tetanus vaccine but only one‐fifth would accept it if offered during an ED visit. ED‐centered efforts to increase uptake should provide messaging to address vaccine hesitancy.